Successful transition to groundwork combat during Junior and Senior Judo World Championships - Nagai, S.; Takito, M. Y.; Calmet, M.; Pierantozzi, E.; Franchini, E. (International Journal of Performance Analysis in Sport, 2019)
The main goal of the present study was to describe the successful transition phases from standing combat to groundwork combat in a high-level judo competition (2017 World Championship) to determine the type of transition (turtle, supine, prone, half-guard, besides, guard, standing and seated) and their rhythms (i.e. time spent by the scoring athletes) mostly used by these athletes. Our sample was based on the junior and senior, male and females, 2017 Judo World Championships. Transition phases (n = 373) that resulted in a score during the junior (n = 179) and senior (n = 194) were analysed. The main findings of this study indicated an immediate link between standing and groundwork actions observed in almost half of the occurrences. Most of the scoring actions (~75%) were achieved through an osae-komi-waza (immobilisation techniques), and these actions were performed mainly when the match was tied (~71%). No significant differences (p > 0.05) were observed between sex and age groups concerning the type of techniques and body position. The different types of transitions were used similarly along the competition phases, indicating that athletes need to be able to cope with different situations in the transition phase to be successful.